Distribution of Fecal Indicator Bacteria in Sediment of Local Open Channels Receiving Johkasou Effluent - Joni Aldilla Fajri; Toshiro Yamada; Ahmad S. Setiyawan; Fusheng Li (Jurnal Sains & Teknologi Lingkungan, 2017)
Onsite wastewater treatment system named Johkasou has been widely applied in the Japanese rural areas, which the effluent is mainly discharged into stream channels. However, Johkasou effluent would potentially be a source of contamination that can deteriorate water and sediment quality of the receiving downstream network. In order to identify the effect of Johkasou effluent particularly in sediment, a study on the distribution of fecal indicators (F-RNA bacteriophages, total coliform (TC), and Escherichia coli [E. coli]) in several sediment spots of local open channels receiving Johkasou effluent was conducted. The results showed that the contents of F-RNA bacteriophages, TC and E. coli in the sediment of open channels were detected in high levels while those contents in the sediment of Johkasou drainage channel were up to two orders magnitude higher than in the open channel. A high number of fecal bacteria in the receiving open channels was majorly influenced by the number of domestic households. Moderate correlations of fecal bacteria indicator with solid sediment and volatile sediment indicate that the sediment particles can be carriers of microbes to the downstream water networks. Therefore, water flushing and hydraulic events are suggested to reduce sediment depth that contained fecal bacteria indicator in the open channel.